Retrospective study of predictors for foot ulceration among diabetic patients attending Kuala Langat Health Centre from 1999 to 2008 - Faridah Karim; Azmi MT (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2009)
Background : Foot ulcers and its complications are an important cause of morbidity and mortality in diabetes. The aim of this retrospective study is to determine the ulcer-free survival in diabetic foot and its relevant predictors in a cohort of diabetic patients in the primary health care setting. Methods : Data of newly diagnosed diabetics (n=1121) who received treatment in five health centers in the district of Kuala Langat, Selangor between 1st January 1999 until the 30th June 2008 were studied. Information was gathered by reviewing patient’s medical records. All patients were followed until 31st December 2008. The duration of ulcer-free survival was measured from the date of being diagnosed as diabetic until the development of the ulcer. Results : The total incidence of diabetic foot ulcer was 9.9% (n=111), with an average annual incidence of 1%. The total incidence of amputation was 1.2%. Mean age of being diagnosed having diabetic was 52+10.7 year old and mean age of being diagnosed having diabetic foot ulcer was 54.68+10.16 year old. The mean for overall ulcer-free survival was 99 months (95%CI:96-102). Male gender (LR=6.56; p=0.01), smokers (LR=3.94; p=0.04), low body mass index (LR=4.45; p=0.03), impaired renal function (LR=5.17; p=0.02) and long duration between follow-up (LR=25.10; p<0.0005) predicted the ulcer-free survival. However, with Cox’s Proportional Hazard Regression analysis factors independently associated to ulcer-free survival were impaired renal function (HR=1.65)(95%CI:1.09,2.46), poor lipid control (HR=2.36)(95%CI:1.03, 5.41) and duration of follow-up more than six months (HR=4.74)(95%CI:2.28,9.86). Other factors studied were not significant. Conclusion : In conclusion, about 1% of primary care health center-based diabetic patients developed new ulcers each year. Renal profile and lipid profile can be used as a predictor to ulcer-free survival for diabetic foot ulcer in the primary health care setting. All patients must be given the appropriate duration of follow-up which should not exceed more than six months with emphasis on defaulter tracing to increase the number of patients free from diabetic foot ulcer.